Analisis Aplikasi PHP-MySql untuk Sistem Informasi Pengarsipan Surat Masuk LPP-RRI Pekanbaru - Noveri Lysbetti Marpaun; Rahyul Amri; Edy Ervianto; Nurhalim Nurhalim (Prosiding SISFOTEK, 2018)
Administration is handled by a Secretary in Public Broadcasting Institution – Radio of Indonesian Republik (LPP-RRI) Pekanbaru. Administration is one field which need to be improved to increase performance of LPP-RRI Pekanbaru in giving services to broadly society in Indonesian area. Incoming Letter Administration is done by recording activity of entering letter manually in an Administration Book of Incoming Letter. Aim of this research is to analize Archieving Information System of Incoming Letters which built on Website of LPP-RRI Pekanbaru by using PHP and MySql for local network. So, Administration of Incoming Letters will not be done manually. Methodology in this research is Analyzing Necessity, Collecting Data, Designing of Recording System from Incoming Letters, Implementing Built System. Method is shown by flowchart and use case diagram. This research can help Secretary in organizing Incoming Letter from year to year completely. So, it can increase Secretary’s productivity. In addition, reporting to Chairmsn of Secretary can be easier because it can be done in form of MS Office. Recording process of Incoming Letters can be done faster because its data kept safety and structurely. Results of research shows that this research works as its framework.